UPAYA PENINGKATAN PARTISIPASI PRIA DALAM PROGRAM METODE OPERASI PRIA (MOP) DI KABUPATEN SUMEDANG - Dhesti Widya Nurhasanah Ningrum; Dede Shinta Berliana; Ihsan Fauzi; Siti Nurcahyati; Thania Wijaya (Journal Of Regional Public Administration (JRPA), 2020)
This study aims to analyze the problem of efforts to increase male participation in a motivational perspective, efforts to increase male participation in a coordination perspective, efforts to increase male participation in a communication perspective and efforts to increase male participation in a supervisory perspective in Sumedang Regency. The method used in the preparation of this administrative research practice report is a qualitative research method (Naturalistic Setting) with descriptive type. The sampling technique used is purposive sampling. With research informants: Head of the Family Planning Division, Head of the Family Planning Service Guarantee Section, and implementing staff of the Family Planning Service Guarantee. Data collection techniques through secondary data collection techniques such as library studies and documentation. In analyzing the data used the Miles and Huberman model with steps: Reduction of data, Presentation of data, Conclution Drawing / Verification, and Triangulation. Based on the results of the study concluded that the effort to increase male participation in the perspective of motivation is quite good but not optimal. This can be seen from the lack of supporting facilities to implement MOP because Sumedang Regency has not been able to implement its own MOP program and the unavailability of operating tools for implementing the MOP. Efforts to increase men's participation in the perspective of good coordination. This can be seen from the existence of internal coordination and external coordination. Efforts to increase male participation in communication perspective can be quite good but not yet optimal, this is known from the ineffectiveness of the media in presenting information such as trends in radio media that only some people listen to. Efforts to increase male participation in the perspective of supervision can be quite good. This can be known from direct and indirect supervision.